Evidence of lower macular pigment optical density in chronic open angle glaucoma. Issue 8 (18th May 2013) - Igras, Estera; Loughman, James; Ratzlaff, Matthew; O'Caoimh, Rónán; O'Brien, Colm
Abstract : Background/aims: Macular pigment (MP) plays an important role in visual function and in the protection of the retina from oxidative damage. It is not known whether glaucoma, a progressive neurodegenerative disease of the optic nerve, is associated with alterations in MP. This study was designed to investigate the relationship, if any, between the optical density of MP optical density (MPOD) and glaucoma. Methods: 40 subjects (23 males, 17 females) with open angle glaucoma (mean age 69 ±11), and 54 normal controls (23 males, 31 females) without ocular disease (mean age 66 ±11), visual acuity (VA) >6/18, were recruited, and underwent a comprehensive eye examination including biomicroscopy, fundoscopy, Goldmann tonometry and visual field assessment, using the 24-2 SITA-fast algorithm on the Humphrey visual field analyser (II-i Series). MPOD, at 0.5° of retinal eccentricity was determined, for all subjects, using heterochromatic flicker photometry. Results: Median (IQR) MPOD for subjects with glaucoma was 0.23 (0.42) compared to 0.36 (0.44) for controls. The difference in MPOD between the glaucoma cases and controls was statistically significant (z=−2.158, p=0.031). There was no significant correlation (p>0.05) between MPOD and disease severity. Conclusions: These findings suggest that MPOD is lower in patients with glaucoma. Further investigation is needed to determine the significance of MP in glaucoma, its relationship to glare symptoms in glaucoma and to assess what role therapeutic strategies aimed at increasing MP levels could have in the management of glaucoma.